2017
DOI: 10.5304/jafscd.2017.072.001
|View full text |Cite
|
Sign up to set email alerts
|

Critical Reflections on the USDA Local Food Economics Toolkit

Abstract: In this paper we report the results of a field test of an economic impact toolkit recently commissioned by the U.S. Department of Agriculture (USDA). The toolkit was created as a guide for food systems organizations to frame issues and collect and analyze data in order to credibly measure economic and other benefits of their initiatives. To test the toolkit, we applied it to an economic contribution study of a local food-buying program in a large regional hospital in Vermont. Our findings indicate that by work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Of the 144 individuals who responded to the survey, 80% agreed that the webinars and/or trainings improved their understanding of how to evaluate economic impacts, and 45% reported that they used information from the Toolkit to support their ongoing work. These observations are similar to feedback obtained from a similar study undertaken by Conner, Becot, and Imrie (2017), which revealed the widespread application of Toolkit principles in community-level food system planning efforts around the country.…”
Section: How Was the Toolkit Disseminated To The Public?supporting
confidence: 86%
“…Of the 144 individuals who responded to the survey, 80% agreed that the webinars and/or trainings improved their understanding of how to evaluate economic impacts, and 45% reported that they used information from the Toolkit to support their ongoing work. These observations are similar to feedback obtained from a similar study undertaken by Conner, Becot, and Imrie (2017), which revealed the widespread application of Toolkit principles in community-level food system planning efforts around the country.…”
Section: How Was the Toolkit Disseminated To The Public?supporting
confidence: 86%
“…Those using the tools presented in this paper should, as Deller et al (2017) suggest, proceed with caution. Collecting sufficient data to conduct credible modification of IMPLAN and adequately account for potential opportunity costs are difficult (Conner et al, 2016;Deller et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While recently published best practices call for adjusting patterns of agricultural producers selling directly to consumers (Jablonski and Schmit, 2016 a ), we did not adjust the production function nor the local purchases percentages of the vegetable and melon farm sector in IMPLAN due to lack of data. This lack of data is a common barrier in economic impact studies of local food initiatives because it is difficult and costly to collect detailed data on the expenditure patterns of farmers (O'hara and Pirog, 2013; Hardesty et al ., 2016; Jablonski et al ., 2016 b ; Conner et al ., 2017).…”
Section: Methodsmentioning
confidence: 99%